2002
DOI: 10.1177/107155760200900508
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Gsα, Connexin-43, Connexin-26, and EP1, 3, and 4 Receptors in Myometrium of Prelabor Singleton Versus Multiple Gestations and the Effects of Mechanical Stretch and Steroids on Gsα

Abstract: These results suggest that the methods whereby stretch can promote myometrial contraction are complex or require additional factors than those tested here. Alternatively, cases of multiple gestation that do not result in preterm labor perhaps compensate for the increased stretch by preventing aberrant expression of the proteins investigated in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…The effect of stretch on Cx43 levels in primary cells has not been assessed. However, myometrial tissue from non-labouring women with singleton and twin pregnancies have been previously compared to show no difference in their Cx43 protein content (Lyall et al , 2002). Together, prolonged in vitro stretch at the cell and tissue level using similar culture media leads to similar consequences for their abundance of classic labour-associated proteins except for PR.…”
Section: Comparison To Stretched Primary Cellsmentioning
confidence: 99%
“…The effect of stretch on Cx43 levels in primary cells has not been assessed. However, myometrial tissue from non-labouring women with singleton and twin pregnancies have been previously compared to show no difference in their Cx43 protein content (Lyall et al , 2002). Together, prolonged in vitro stretch at the cell and tissue level using similar culture media leads to similar consequences for their abundance of classic labour-associated proteins except for PR.…”
Section: Comparison To Stretched Primary Cellsmentioning
confidence: 99%
“…In vitro stretch models of human myometrial cells and strips (Moraitis et al 2015) showed increased OTR expression and responsiveness, respectively, while in vivo, acute uterine stretch increases PG synthesis (Manbe et al 1982). Interestingly, no difference in prolabour gene expression was seen when comparing twin and singleton pregnancies (Lyall 2002). Equally, excessive uterine stretch, seen in polyhydramnios, multiple pregnancy or a singleton pregnancy in a unicornuate uterus are all associated with increased rates of PTL (Rodriguez 1992, Reichman et al 2009, Conde-Agudelo & Romero 2014 (Fig.…”
Section: Physiologymentioning
confidence: 99%
“…infection and shortened cervix, but it is plausible for there to be distinct mechanisms, e.g. increased uterine distension, leading to the upregulation of proteins and pathways promoting contractility (Lyall et al 2002). Both chronic and acute stretch can increase excitability and initiate parturition (Wu et al 2012).…”
Section: Figure 2 Proposed Schematic Diagram To Show How Lactate Andmentioning
confidence: 99%
“…increased uterine distension, leading to the upregulation of proteins and pathways promoting contractility (Lyall et al . ). Both chronic and acute stretch can increase excitability and initiate parturition (Wu et al .…”
Section: Introductionmentioning
confidence: 97%